A computed tomography-based retrospective study on the foramen ovale and foramen spinosum in a Nigerian population - Beryl Shitandi Ominde; Dorcas Eruwu Odjegba; Joyce Ekeme Ikubor; Faithful Orovwoghene Omoro; Patrick Sunday Igbigbi (MGM Journal of Medical Sciences)
Background: This study investigated the shapes and dimensions of the foramen ovale (FO) and foramen spinosum (FS) in a specific population sample from Delta State, Nigeria, emphasizing their significance in various neurosurgical procedures. Materials and Methods: Following ethical clearance, this retrospective study analyzed 250 brain computed tomography (CT) images from the Radiology Department of a teaching hospital in Delta State, Nigeria. The sample included images from 100 females and 150 males, all aged 18 years or older. The dimensions of the FO and FS were measured on axial sections using a standardized protocol. Statistical analyses were conducted with Statistical Package for Social Sciences (IBM, Chicago, Illinois, United States) software, categorizing data by gender and age groups. Inferential statistics, including Student t test, analysis of variance, and Pearson’s correlation, were performed, with findings considered significant at P < 0.05. Results: The predominant shapes of the FO and FS were oval and round, respectively. Significant side differences were observed in the length of the right FS (P = 0.040). Gender differences were noted in the length of the bilateral FO (P = 0.010) and the width of the left FO (P = 0.001). A significant correlation with age was found for the width of the left FO (P = 0.006) and the distance from the right FO to FS (P = 0.037). The FS was absent in 24 cases (9.6%). Conclusion: This study highlights age-, side-, and gender-related differences in the shapes and dimensions of the FO and FS. It emphasizes the importance of precise preoperative radiological assessments to ensure optimal outcomes for neurosurgical planning.